AB0555 Are there differences in biomarkers of cartilage and bone turnover between patients with familial versus sporadic early spondiloarthritis?. (23rd January 2014) - Almodovar, R.; Rios, V.; Ocaña, S.; Gobbo, M.; Casas, M. L.; Zarco, P.; Juanola, X.; ,
Abstract : Objectives: Our purpose was analyze potential differences in biomarkers of cartilage and bone turnover between patients with familial early spondyloarthritis (SpA) and sporadic early EspA. Methods: A cross-sectional study of baseline visits from 60 patients included in Esperanza program was performed. Patients analyzed were under 45 years old, with onset symptoms within the range of 3 to 24 months. All patients included met the following criteria: a) inflammatory back pain, or b) symmetric arthritis, or c) back pain /articular pain, in addition to at least one of the following: a) psoriasis, b) inflammatory bowel disease (IBD), c) anterior uveitis (AU), d) radiographic sacroiliitis, e) family history of spondylitis, psoriasis, IBD, or AU, f) HLA-B27 positive. Data collected: social/demographic, ESR, CRP, HLA-B27, BASDAI, ASDAS, BASFI, total BASRI and ASQol. MRI of sacroiliac joints (SIJs) was performed on 32 patients and activity was defined according to the ASAS Group definitions for active lesions on MRI. Serum MMP-3 (ELISA), CTX (Cromatogrphic), hsCRP (Nefelometric) and urinary D-pyridoline (QLIA) were measured in all patients. Familial early spondyloarthritis (EspA) was considered when the patient confirmed having first-degree relatives with diagnostic of spondiloarthropathy, defined by ESSG criteria. Analysis: Chi square was used to compare rates and U de Mann-Whitney to analyze continuous variables. Results: At baseline, a total of 60 patients diagnosed of early SpA were included: 26 male (43.3%) and 34 female (56.7%), with age 32.4± 6.7 years and disease duracion of 12.4± 6.8 months. Twenty two percent of patients had axial affectation, 63.6% peripheral, 4.5% mixed and 9% enthesitic pattern. HLA B27 was positive in 26.6% patients. Thirteen percent had psoriasis. Twenty one patients (35%) had active sacroiliitis by MRI. The values (mean ± SD) were: nocturnal pain (cm) 4.5± 2.6; BASDAI (cm) 4.3 ± 2.4; ASDAS 2.2 ± 1.1; ESR (ml/h)14.7± 14.6; CRP (mg/L) 5.3± 9.4 ; BASFI (cm) 2.7± 2.4; total BASRI 0.68 ±1.2 and ASQol 6.7± 5. The frecuency of familial early SpA was of the 8.3% (n=5). The values of biomarkers between sporadic vs familial early SpA (mean ± SD) were: MMP-3 (36, 2± 47.2 vs 15.8± 8.7 p= 0.09); CTX : (0.38± 0.31 vs 0.26± 0.14, p= 0.28); D- pyridoline: (12.7± 7.7 vs 11.2± 3.8, p= 0.98); hs PCR: (0.6± 0.5 vs 1± 4.8 p= 0.9). Conclusions: In our study, MMP-3 showed upward trend to higher levels in patients with sporadic early SpA. Which may indicate higher radiographic damage in these patients. Previous papers found correlation MMP-3 with radiographic damage (1 ). In the rest of biomarkers we didn't objetive differences between patients with sporadic versus familial early spondiloarthritis. "Esperanza Program has been supported by an unrestricted grant from Pfizer" References: Maksymowych WP, Landewé R, Conner-Spady B, et al. Serum matrix metalloproteinase 3 is an independent predictor of structural damage progression in patients with ankylosing spondylitis. Arthritis Rheum 2007, 56:1846-53. Disclosure of Interest: None Declared